Pollution and risk assessment of heavy metals in Zuoxiguo antimony mining area, southwest China. Issue 1 (31st December 2023) - Bai, Ziyou; Wu, Fuzhong; He, Yinping; Han, Zhiwei
ABSTRACT: We collected tailings samples to assess and analyze the concentrations of heavy metals, pollution levels, and the risks posed by heavy metals in the tailings of the Zuoxiguo antimony mine to ecological and human health. The samples were selected by employing the serpentine sampling method, which were treated heavy-metal digestion method. Cu, Cr, Cd, and Pb were determined via inductively coupled plasma mass spectrometry, As and Sb were identified through atomic fluorescence, the average concentration of heavy metals in the tailings is: Sb (5902.77 mg/kg)>As (412.53 mg/kg)>Zn (155.42 mg/kg)>Cr (143.32 mg/kg)>Cu (92.68 mg/kg)>Pb (48.49 mg/kg)>Cd (3.29 mg/kg). The average Nemerow pollution index (NPI) was 553.06, indicating a high level of pollution. The average integrated ecological risk index (RI) result was 5395.94, indicating a serious threat to the study area's ecology. The Non-carcinogenic health-risk index (HQ) suggested that all heavy metals posed a higher risk to children than to adults under different modes of exposure, with oral intake of Sb and As posing a non-carcinogenic risk to both adults and children, For adults, HQing value of Sb and As are 22.07 and 2.13, respectively; for child, HQing value of Sb and As are 178 and 16.29, which are exceeding limitation of 1. Dermal exposure posing a non-carcinogenic risk to child, for child, HQderm value of Sb and As are 14.96 and 3.32, which are also exceeding limitation of 1. The findings suggest that Sb and As pose serious threats to both the ecological environment and human health and that the local government should focus on Sb and As management for regions.